The Construction, Mobilization and Limits of South Asianism in North America - Anouck Carsignol (South Asia Multidisciplinary Academic Journal)
Traditionally, states see the diaspora at best, as an instrument of long distance nationalism, and at worst, as a source of internal conflict. Yet, migrants who define themselves as South Asians in North America transcend subnational and national borders in the name of a pan-regional identity. Beyond cultural or ethnic commonalities anchored in the Indian subcontinent, ‘South Asianism’ is emerging as a form of political consciousness and radical activism, mobilized against racial discrimination and socio-economic injustice. This article, based on ethnographic fieldwork combined with an analysis of digital networks, explores the construction and the limits of the South Asian category, identity and ideology in North America. It sheds new light on the paradoxes of a transnational, post-diasporic mobilization, which claims roots in the subcontinent but is essentially anchored in the host society, where it is dedicated to migrants’ cultural affirmation, civic participation and socio-economic empowerment.